Surface studies of potentially corrosion resistant thin film coatings on chromium and type 316L stainless steel - Johnson, Stephanie Lee (Kansas State University, 2006)
This work is a detailed study of the interaction between two phosphorous-containing acids and the metals chromium and 316L stainless steel. The objective of this work is to investigate the formation of unique thin films on the two metals and to probe the surface chemistry of these films through the use of core level and valence band X-ray photoelectron spectroscopy (XPS). Chromium forms a wide array of oxides and can exist at several valencies. Valence band XPS is used in conjunction with band structure and multiple scattered wave X[alpha] calculations to distinguish which states are present in the resultant films. Both 99.99% chromium and 316L stainless steel foils were treated with orthophosphoric acid and 1-hydroxyethylidene-1,1-diphosphonic acid, otherwise known as etidronic acid. Two methods developed in the Sherwood research laboratory for forming oxide-free films on metal surfaces are utilized in this work. Core level XPS results did not provide sufficient information to draw conclusions regarding the products formed in the reactions. The valence band results showed clear evidence of multiple forms of phosphates forming on the metal surfaces as evidenced by the subtle differences in separation between the phosphorous 3p and 3s peaks as well as differences in separation between the O2s and phosphorous 3s peaks. The Valence Band XPS results were interpreted by X-[alpha] cluster and band structure calculations. Films formed on chromium foil from the orthophosphoric acid were found to be condensed phosphates that are stable in air. Etidronic acid formed very thin phosphate films on chromium with both treatment methods as well as on 316L stainless steel when the bench top method was applied. Treatment of etched 316L steel in the anaerobic cell generated an etidronate film. This sample was the only etidronate film formed, all other etidronate-based films were generated from disassembled portions of the etidronate ion to form phosphate films.
Keywords: Materials chemistry; Surface science; Chromium phosphates; X-ray photoelectron spectroscopy; Chemistry, Analytical (0486); Chemistry, Physical (0494)